2019
DOI: 10.3847/1538-4357/ab2118
|View full text |Cite
|
Sign up to set email alerts
|

How Do Galaxies Trace a Large-scale Structure? A Case Study around a Massive Protocluster at Z = 3.13

Abstract: In the hierarchical theory of galaxy formation, a galaxy overdensity is a hallmark of a massive cosmic structure. However, it is less well understood how different types of galaxies trace the underlying large-scale structure. Motivated by the discovery of a z = 3.13 protocluster, we examine how the same structure is populated by Lyα-emitting galaxies (LAEs). To this end, we have undertaken a deep narrow-band imaging survey sampling Lyα emission at this redshift. Of the 93 LAE candidates within a 36 ′ ×36 ′ (70… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 119 publications
(182 reference statements)
9
39
1
1
Order By: Relevance
“…For instance, Shimakawa et al (2017) have found a few Mpc deviation of LAEs' density peak in a z = 2 protocluster from that of Hα-emitting galaxies, which are normal star-forming galaxies commonly seen at high redshifts. A similar offset from continuum-selected galaxies has also been reported (Overzier et al 2008;Toshikawa et al 2016;Shi et al 2019). More importantly, Momose et al (2020) have suggested that the peak of LAEs' distribution does not match that of intergalactic neutral hydrogen (IGM Hi).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…For instance, Shimakawa et al (2017) have found a few Mpc deviation of LAEs' density peak in a z = 2 protocluster from that of Hα-emitting galaxies, which are normal star-forming galaxies commonly seen at high redshifts. A similar offset from continuum-selected galaxies has also been reported (Overzier et al 2008;Toshikawa et al 2016;Shi et al 2019). More importantly, Momose et al (2020) have suggested that the peak of LAEs' distribution does not match that of intergalactic neutral hydrogen (IGM Hi).…”
Section: Introductionsupporting
confidence: 81%
“…Our results also indicate that LAEs may not faithfully trace matter distribution, unlike O3Es and continuumselected galaxies. Some observational studies have found a 3 − 15 h −1 cMpc offset between the overdensity peaks of LAEs and other galaxy populations (Toshikawa et al 2016;Shimakawa et al 2017;Shi et al 2019). Given the anisotropy of Hi density distribution over r = 3 − 5 h −1 cMpc found in this study, the discordance reported by those previous studies can be, at least partly, explained by the selection bias.…”
Section: Discussion and Summarycontrasting
confidence: 52%
See 1 more Smart Citation
“…Deep narrow-band imaging surveys have recently demonstrated the utility of Lyα emission as tracers of the large-scale structure in the distant universe. Massive protocluster sites are found to be significant overdensities of LAEs (Steidel et al 2000;Lee et al 2014b;Bȃdescu et al 2017;Shi et al 2019a). In several protoclusters, filamentary structures traced by LAEs stretch out tens of Mpcs from a protocluster (Matsuda et al 2005;Dey et al 2016a), mirroring the expectation of dark matter structures around a cluster-sized halo.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of ELGs in overdense regions, can be used to infer the underlying dark matter (DM) distribution, and how galaxy properties relate to the environment in which they reside (Mo et al 2004;Cooray 2005;Overzier et al 2006;Orsi et al 2016;Ota et al 2018;Shi et al 2019;Gonzalez-Perez et al 2020). In particular, the way in which the environment of protoclusters affects the emission of ELG at high redshift is still a matter of debate (see Overzier 2016, for a review).…”
Section: Introductionmentioning
confidence: 99%